History and politics : remembrance as legitimation - Kącka, Katarzyna, 1977- (CGS studies, 2017)
History and politics are interlinked with unbreakable bonds, as is manifested primarily in the use of historical arguments in political disputes. Regardless of the ideological views represented, time period, and geographical location, politicians consistently and frequently use such arguments with a high degree of effectiveness. Driven by a variety of motives, they use the category of the past, (re)interpret it, and decide what should be remembered and what should be removed from the so-called collective memory. In practice, this means that a properly prepared and delivered narrative of the past can become a powerful instrument in the hands of the ruling class, influencing the social and political reality of the country concerned. Control of the past and its correct reconstruction can thus effectively contribute to gaining, boosting, and consolidating power by a political entity. An appropriately shaped awareness of the past thus serves an only ancillary role to politics, satisfying social expectations and ideological visions. Thus, the past, or rather the memory of it, when becoming a topic of interest in the domain of politics, forces the creators of the politics of history to improve the tools and mechanisms they wield to ensure its more efficient use. --